Rebranding - A Boon to Survive - Singh, Harvinder; Dharamveer (Indian Journal of Marketing, 2011)
One of the key decisions a company makes in regards to marketing relates to the brand. Branding is critical to product identification and is a key factor in differentiating a product from its competition. A brand represents a company’s promise to its customers and tells the world who the company is and what it delivers. It’s the latest trend and it’s coming at you on a regular basis-"Rebranding" is being used extensively in the corporate world and it is going to last in the distant future. Not only do companies use the process of rebranding, but countries, wars, and celebrities are using the process as well to distribute or promote themselves with a different identity. Some companies have even rebranding several times. The driver behind frequent rebranding may be due to the fact that consumers are fickle. If your product is not the newest and the best, then consumer will try something else. The consumers expect innovation...if you don’t keep up with new improved formulas and fashionable logos, then you will lose customers. This paper will attempt to identify rebranding and its elements and outline the mistakes to avoid when rebranding in an effort to answer the question "Does rebranding really work?".